Supervisi Pendidikan Kepala Madrasah dalam Meningkatkan Kompetensi Akademik Guru: Studi Kasus Nilai-nilai Organisasi NWDI di MA NWDI Wakan - Kamaruddin Kamaruddin (PALAPA, 2025)
The quality of teachers’ academic competence in madrasah is often suboptimal due to weak implementation of educational supervision and limited integration of organizational values as the basis for professional development, as reflected in MA NWDI Wakan, which continues to face challenges in lesson planning, variation of teaching methods, classroom management, and authentic assessment. This study aimed to analyze how the madrasah principal implements NWDI value-based educational supervision to improve teachers’ academic competence. A qualitative approach with a case study design was employed, using in-depth interviews, classroom observations, and document analysis, which were analyzed qualitatively. The findings show that supervision is systematically designed through an analysis of teachers’ needs and the reinforcement of the values of sincerity, trustworthiness, deliberation, and togetherness as the foundation for conducting clinical supervision. Supervision is implemented through non-authoritative observation, reflective dialogue, coaching, and mentoring, while evaluation is holistic and followed by follow-up actions in the form of workshops, team teaching, and re-supervision. The results indicate a significant improvement in the quality of lesson plans (RPP), the variety of active learning methods, classroom management, and the use of authentic assessment rubrics. The study concludes that value-based and collaborative supervision is effective in strengthening teachers’ professionalism and improving the quality of instructional services in madrasah. The implications highlight the need to reinforce the integration of organizational values in supervision, expand continuous training for madrasah principals, and consider replicating this supervision model in other Islamic madrasah contexts.